Multisensor classification system for triggering FES in order to support voluntary swallowing - Benjamin Riebold; Holger Nahrstaedt; Corinna Schultheiss; Rainer O. Seidl; Thomas Schauer (PAGEPress Publications, 2016)
In dysphagia the ability of elevating the larynx and hyoid is usually impaired. Electromyography (EMG) and Bioimpedance (BI) measurements at the neck can be used to trigger functional electrical stimulation (FES) of swallowing related muscles. Nahrstaedt et al.1 introduced an algorithm to trigger the stimulation in phase with the voluntary swallowing to improve the airway closure and elevation speed of the larynx and hyoid. However, due to non-swallow related movements like speaking, chewing or head turning, stimulations might be unintentionally triggered. So far a switch was used to enable the BI/EMG-triggering of FES when the subject was ready to swallow, which is inconvenient for practical use. In this contribution, a range image camera system is introduced to obtain data of head, mouth, and jaw movements. This data is used to apply a second classification step to reduce the number of false stimulations. In experiments with healthy subjects, the amount of potential false stimulations could be reduced by 47% while 83% of swallowing intentions would have been correctely supported by FES.